2022
DOI: 10.3389/fendo.2022.897797
|View full text |Cite
|
Sign up to set email alerts
|

Combined Use of Autofluorescence and Indocyanine Green Fluorescence Imaging in the Identification and Evaluation of Parathyroid Glands During Total Thyroidectomy: A Randomized Controlled Trial

Abstract: Background and objectivesAccurate identification and evaluation of the parathyroid glands (PGs) intraoperatively is critical to reduce the incidence of postoperative hypoparathyroidism after total thyroidectomy. Near-infrared fluorescence imaging (NIFI), including the autofluorescence (AF) and indocyanine green fluorescence (ICGF) imaging, is a promising technique to protect PGs. This study aimed to assess whether the combined use of AF and ICGF could reduce the incidence of postoperative hypoparathyroidism an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 25 publications
0
25
1
Order By: Relevance
“…Parathyroid glands were routinely identified by the naked eye or ICG combined with autofluorescence if it was difficult to evaluate their location and blood supplies. Detailed methods of ICG combined with autofluorescence were described in our previous study (12). If the blood supply was deemed sufficient by the surgeon's verdict, the suspected parathyroid would be preserved in situ.…”
Section: Parathyroid Gland Identification and Transplantationmentioning
confidence: 99%
“…Parathyroid glands were routinely identified by the naked eye or ICG combined with autofluorescence if it was difficult to evaluate their location and blood supplies. Detailed methods of ICG combined with autofluorescence were described in our previous study (12). If the blood supply was deemed sufficient by the surgeon's verdict, the suspected parathyroid would be preserved in situ.…”
Section: Parathyroid Gland Identification and Transplantationmentioning
confidence: 99%
“…In thyroid and parathyroid surgery, autofluorescence has been shown to reliably improve identification of the thyroid glands and differentiate between the parathyroid glands and surrounding tissues, including the thyroid gland, with randomized controlled trials demonstrating decreased rates of hypocalcemia following thyroidectomy [31,32] . Meanwhile, ICG FA may provide surgeons with information on the perfusion status of the parathyroid glands in addition to helping to identify them during parathyroidectomy.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were supported by the PARAFLUO multicenter randomized trial comparing rates of hypocalcemia (corrected calcium < 8.0 mg/dL) on postoperative day (POD) 1 or 2. In that study, Benmiloud et al [32] randomized 241 patients to conventional thyroidectomy vs. NIRAF-assisted thyroidectomy and found that the rates of temporary hypocalcemia were 9.1% for the NIRAF group and 21.7% for the controls (P = 0.007), though they did not detect a significant difference in permanent hypocalcemia (0% vs. 1.6%, respectively). These findings persisted in multivariate analysis, with an odds ratio of 0.35 for hypocalcemia in the NIRAF group.…”
Section: Autofluorescencementioning
confidence: 99%
See 2 more Smart Citations